Can yield, soil C and aggregation be improved under long‐term conservation agriculture in the eastern Indo‐Gangetic Plain of India? - Mondal, Surajit; Mishra, Janki Sharan; Poonia, Shish Pal; Kumar, Rakesh; Dubey, Rachana; Kumar, Santosh; Verma, Mausam; Rao, Karnena K.; Ahmed, Akram; Dwivedi, Sharad; Bhatt, Bhagwati Prasad; Malik, Ram Kanwar; et al. (Wiley, 2021)
Deteriorating soil health, diminishing soil organic carbon (SOC), development of subsurface hard compact layer and declining system productivity are barriers to achieving sustainable production in the traditional rice–wheat cropping system (TA) in the eastern Indo‐Gangetic Plain of India. Conservation agriculture (CA), which favours minimum soil disturbance, crop residue retention and crop diversification could be a viable alternative to the TA to address most of those major problems. With that in mind, a long‐term experiment is being implemented at ICAR‐RCER, Patna, Bihar, India, with four treatments: (a) TA, (b) full CA (fCA) and (c and d) partial CA (pCA1 and pCA2), differing in crop establishment methods, cropping system and crop residue management in a randomized complete block design. Measurement of soil health parameters was carried out in the 11th year of the experiment. The results revealed a beneficial effect of CA and 46 and 40% increase in SOC concentration and stock, respectively, under fCA over TA in the 0–7.5‐cm soil layer. The effect of partial CA (pCA1 and pCA2) was variable, but an increasing trend was always observed under pCA compared to TA. There was an enrichment in SOC content of aggregates under CA irrespective of size class; however, no relation was found between SOC content and aggregate diameter. The contribution of macroaggregates to SOC stock was larger (36–66%) under CA in the 0–7.5‐cm soil layer. Adoption of CA improved the macroaggregate content, MWD and GMD of aggregates, and aggregation ratio. Soil macropore content was greater under fCA, whereas other parameters were similar among treatments. The impact of CA was mostly limited to 0–7.5 cm soil layer and a maximum up to 15 cm soil depth while evaluation until 60 cm soil depth was realized. The yield of rice in CA was comparable to or higher than in TA, whereas the system rice equivalent yield was always higher (38–53%) under CA than under the conventional practices. Therefore, a CA‐based cropping system must be encouraged, to increase SOC status, improve aggregation stability and, consequently, sustain or increase system productivity, in order to achieve food and nutritional security in the eastern Indo‐Gangetic Plain of India.Highlights Effects of long‐term conservation agriculture (CA) on soil C, aggregation and yield were evaluated. CA improved SOC concentration and stock by 46 and 40%, as well as macroaggregate SOC stock by 36–66%. Macro‐aggregation and mean weight diameter improved in CA but was mostly limited to a shallow soil depth. CA can be promoted for sustainability of a rice–wheat system due to higher productivity (38–53%).